Tafsir Ayat Ahkam Surah An-Nisa Ayat 3: Etika Poligami dan Hikmahnya Dalam Syari’at Islam - Mahfud Mahfud; Muhammad Qudwah I’tishom Billah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2022)
The theme of polygamy is becoming more and more hotly discussed because of the many cases of polygamy that have arisen, causing hatred and separation in the midst of the family. Among the opinions that support polygamy, they use the Qur'an as a proof. Likewise, those who reject polygamy also use the Qur'anic text as a basis. The verse of the Qur'an that some people who support polygamy rely on is Surah An-Nisa [4]: ​​3. They interpret the verse with a clear meaning contained in the words. This study uses research using qualitative research with a library research approach. Polygamy is one of the shari'a of fixed Islamic shari'a. This has been stated in the letter an-Nisa [4]: 3. However, in its interpretation, the scholars have different opinions whether the order is mandatory or not. Scholars from the Zahiriyyah consider it obligatory, while the majority of scholars consider it permissible depending on the circumstances of the family being lived.